Placental Growth Factor Level is Lower in Early-Onset Preeclampsia, while Tumor Necrosis Factor Alpha Level does not Show any Difference between Early and Late Onset Preeclampsia - Ekapatria, Christofani (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: To analyze the difference of PlGF and TNF-Î± serum level between early-onset and late-onset preeclampsia. Method: This is a cross-sectional analytic comparative study comparing serum level of PlGF and TNF-Î± between groups with earlyand late-onset preeclampsia. Each group consists of 32 subjects who met inclusion criteria and presented to Dr. Hasan Sadikin Hospital or its district hospitals in September - November 2012. Statistical analysis was performed with Kolmogorov Smirnov test, Saphiro-Wilk test, and non-parametric Mann-Whitney test. Result: Mean of PlGF serum level in the group with early-onset preeclampsia is 53.0344Â±38.07140 pg/ml, while mean of which in the group with late-onset preeclampsia is 241.8063Â±192.8373 pg/ml (p